The Critical Role of Electrolyte Gating on the Hydrogen Evolution Performance of Monolayer MoS 2 - Liu, Xiangye; Li, Baichang; Li, Xufan; Harutyunyan, Avetik R.; Hone, James; Esposito, Daniel V. (Nano letters, 2019)
According to density functional theory, monolayer (ML) MoS is predicted to possess electrocatalytic activity for the hydrogen evolution reaction (HER) that approaches that of platinum. However, its observed HER activity is much lower, which is widely believed to result from a large Schottky barrier between ML MoS and its electrical contact. In order to better understand the role of contact resistance in limiting the performance of ML MoS HER electrocatalysts, this study has employed well-defined test platforms that allow for the simultaneous measurement of contact resistance and electrocatalytic activity toward the HER during electrochemical testing. At open circuit potential, these measurements reveal that a 0.5 M H SO electrolyte can act as a strong p-dopant that depletes free electrons in MoS and leads to extremely high contact resistance, even if the contact resistance of the as-made device in air is originally very low. However, under applied negative potentials this doping is mitigated by a strong electrolyte-mediated gating effect which can reduce the contact and sheet resistances of properly configured ML MoS electrocatalysts by more than 5 orders of magnitude. At potentials relevant to HER, the contact resistance becomes negligible and the performance of MoS electrodes is limited by HER kinetics. These findings have important implications for the design of low-dimensional semiconducting electrocatalysts and photocatalysts.